Enhanced proton conduction by post-synthetic covalent modification in a porous covalent framework - Samanta, Partha; Desai, Aamod V.; Anothumakkool, Bihag; Shirolkar, Mandar M.; Karmakar, Avishek; Kurungot, Sreekumar; Ghosh, Sujit K. (Journal of Materials Chemistry A, 2017)
A highly chemically stable porous covalent framework (PCF-1) based on ether linkages has been synthesized, which exhibits no loss up to similar to 500 degrees C along with retention of integrity under acidic, basic and oxidative reagent conditions. Owing to its thermal and chemical stability, post-synthetic covalent modification was executed for the introduction of pendant sulphonic acid (-SO3H) groups. The covalently modified compound (PCF-1-SO3H) presents a remarkably high conductivity (ca. 0.026 S cm(-1)), with an similar to 130 fold enhancement in proton conductivity over the parent compound. This value is comparable with those of commercially used Nafion-based proton conducting materials and stands as the highest known value in the regime of post-synthetically modified porous organic frameworks. It is noteworthy to mention that PCF-1 is stable in both acidic and alkaline media, which is not commonly observed for most of the porous materials trialed as proton conducting materials, including metal organic frameworks.